The Correlation Between Grammar Mastery and Writing Ability of the Eight Grade Students of SMP Negeri 1 Tolitoli - Aprillia Pramudita; Ismail Yunus H; Jaya (Universitas Insan Budi Utomo, 2026)
: The researcher aims to determine whether there is a significant correlation between grammar mastery and writing ability of eighth grade students of SMP Negeri 1 Tolitoli. This study uses a correlational research design. The sample consists of 25 students of class VIII H who were selected purposively. The data were analyzed statistically using SPSS 25. The results of the study indicate that there is a correlation between grammar mastery and writing ability, with a correlation coefficient of 0.548 which is in the range of 0.40–0.599, which indicates a moderate correlation. The data shows that the Sig. (2-tailed) value = 0.006, which is smaller than 0.05. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. These results indicate that there is a significant correlation between grammar mastery and writing ability.